Implications of the Preseidential Threshold Based on the 1945 Constitutional Law Article 6A After the Enactment of Law Number 7 of 2017 (Concerning General Elections) - Hilmawan, Fajrin; Suparji, Suparji; Hidayat, Yusup (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
In essence, general elections or general elections are a means of democracy which is essentially to organize a state government by, from and for the people or in other words to realize sovereignty. Because basically, the constitution is an important document which contains basic regulations regarding the structure government, rights and obligations as well as limitations on state authority. This resulted in the euphoria of democracy and freedom that permeated all life nation and state so that it has an impact on efforts to make changes or changes to the constitution or the basis of state administration. Democracy is closely related with the principle of administering the rule of law on the grounds that in literacy democracy, general elections are one of the principles of the rule of law. This research is a normative juridical research method, research that uses regulations legislation, with a legal theory approach, so that it can help complete the writing of this research.